2013
DOI: 10.1089/aid.2012.0071
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: T Cell Activation in HIV-1/Herpes Simplex Virus-2-Coinfected Kenyan Women Receiving Valacyclovir

Abstract: Herpes simplex virus-2 (HSV-2) suppression with acyclovir or valacyclovir reduces HIV-1 viral RNA levels; one hypothesis is that HSV-2 suppression reduces immune activation. We measured T cell immune activation markers among women participating in a randomized placebo-controlled trial of valacyclovir to reduce HIV-1 RNA levels among pregnant women. Although valacyclovir was associated with lower HIV-1 RNA levels, the distribution of both CD4(+) and CD8(+) CD38(+)HLA-DR(+) T cells was not different among women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recent global estimates of prevalent HSV-2 in adults aged 15–49 years in 2012 indicated prevalence in females of 14.8 % and in males of 8.0 %; in Europe the estimate was 10 % for women and 4 % for men [ 20 ]. High HSV-2 prevalence is reported in women living with HIV, for example, 86 % of HIV-positive pregnant women in a Nairobi study [ 21 ]. In a Canadian study of Africa/Caribbean-born women, prevalence of HSV-2 infection was 86 % in HIV-positive and 47 % in HIV-negative women [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent global estimates of prevalent HSV-2 in adults aged 15–49 years in 2012 indicated prevalence in females of 14.8 % and in males of 8.0 %; in Europe the estimate was 10 % for women and 4 % for men [ 20 ]. High HSV-2 prevalence is reported in women living with HIV, for example, 86 % of HIV-positive pregnant women in a Nairobi study [ 21 ]. In a Canadian study of Africa/Caribbean-born women, prevalence of HSV-2 infection was 86 % in HIV-positive and 47 % in HIV-negative women [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purported explanation for this negative finding is the considerably lower concentrations of acyclovir achieved in the clinical setting compared with the laboratory studies. Still another possibility is that acyclovir could attenuate HIV disease progression by decreasing HSV-2-related immune activation, although two studies have recently shown no benefit of valacyclovir on a variety of inflammatory markers [ 32 , 33 ]. Further data are needed to clarify the relationship between HSV-2, anti-herpes medications and HIV viral load.…”
Section: Discussionmentioning
confidence: 99%